Gout Remission as a Goal of Urate-Lowering Therapy: A Critical Review - Adwoa Dansoa Tabi-Amponsah; Sarah Stewart; Graham Hosie; Lisa K. Stamp; William J. Taylor; Nicola Dalbeth (Pharmaceuticals, 2023)
Urate-lowering therapies for the management of gout lead to a reduction in serum urate levels, monosodium urate crystal deposition, and the clinical features of gout, including painful and disabling gout flares, chronic gouty arthritis, and tophi. Thus, disease remission is a potential goal of urate-lowering therapy. In 2016, preliminary gout remission criteria were developed by a large group of rheumatologists and researchers with expertise in gout. The preliminary gout remission criteria were defined as: serum urate < 0.36 mmol/L (6 mg/dL); an absence of gout flares; an absence of tophi; pain due to gout < 2 on a 0–10 scale; and a patient global assessment < 2 on a 0–10 scale over a 12-month period. In this critical review, we describe the development of the preliminary gout remission criteria, the properties of the preliminary gout remission criteria, and clinical studies of gout remission in people taking urate-lowering therapy. We also describe a future research agenda for gout remission.